The Article COMPARISON OF LX-8000R AND URISED 2 FULL-AUTOMATED URINE ANALIZERS WITH MANUAL MICROSCOPIC EXAMINATION - canpolat erkan, revşa evin; Aslan, Özgür (Journal of Medical Biochemistry, 2021)
Background: Urinalysis has an important place in evaluating kidney and urinary tract infections. Automated urine analyzers enhance productivity and turnover in laboratories and economize time and labor required for analysis. In the present study, we evaluated and compared analytic and diagnostic performance of UriSed2 with LX-8000R, which is a novel image-based automated urine sediment analyzer.Methods: A total of 178 urine samples sent to our laboratory were evaluated by the two urine analyzers and standard manual microscopy. Precision and comparison studies were done in accordance with CLSI guidelines.Results: Sensitivity assessment revealed similar outcomes with both UriSed2 and LX-8000R devices for erythrocyte count (RBC), whereas UriSed2 device yielded higher outcomes for leukocyte count (WBC) and epithelial cells (EPI) than LX-8000R analyzer. Specificity of UriSed2 for WBC and RBC was higher than that of LX-8000R device. According to Gamma statistics, both urine analyzers showed perfect consistency for WBC, RBC and EPI cell counts. Manuel microscopy revealed statistically significant correlation between LX-8000R and UriSed2 in terms of WBC and RBC. Manual evaluation by Bland-Altman analysis demonstrated lower WBC and RBC values and higher EPI as compared to both UriSed2 and LX-8000R devices. As the result of Passing-Bablok regression analysis, both devices were found to be inconsistent with manual microscopy.Conclusion: We think that evaluation of automated urine analyzers will be more meaningful when they are evaluated together with urine samples and patient clinic in addition to comparing with manual microscopy.
Keywords: Automated urine analyzer, LX-8000R, Urised 2, manuel microscopy